Analisis Implementasi Pemungutan Pajak Restoran Dalam Meningkatkan Penerimaan Pajak Daerah Pada Unit Pelayanan Pajak Dan Retribusi Daerah Gambir Jakarta Pusat Tahun 2018 - Anita Carlina; Edy Edy (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
In the Regional Regulation, the Government has issued a policy as outlined in the Regional Regulation No. 11 of 2011 on Restaurant Tax. The limitation of the Gross Income in the Regional Regulation is imposed on restaurants with sales value above Rp.200,000,000,-/year. This study aimed to analyze the justification and implementation of restaurant tax collection in increasing regional revenue and to analyze the obstacles and appropriate efforts for restaurant entrepreneurs in increasing restaurant tax revenue in the Administrative City Tax Service Unit of Central Jakarta. The method used in this study was qualitative research with descriptive research. The results of this study showed that in the policy of restaurant tax collection, other than those already applied to restaurants with business permits, there are still potential tax objects from restaurant tax that have not yet been collected with a rate of 10%. Furthermore, restaurant tax collection affects restaurant tax revenue at the Administrative City Tax Service Unit of Central Jakarta. However, with further consideration, it is necessary to conduct research from the Administrative City Tax Service Unit of Central Jakarta regarding the problem of restaurants that do not have a business permit and in providing socialization of the benefits of having a business permit. Then there needs to be an acceleration of legal settlement related to the material test on Regional Regulation No. 11 of 2011 on Restaurant Tax to obtain legal certainty for the object of restaurant tax and to increase restaurant tax collection in order to increase regional income.